THE INFLUENCE OF EXTRACURRICULAR ACTIVITIES, TEACHER TEACHING STYLES AND LEARNING MOTIVATION ON LEARNINGACHIEVEMENT IN SMA SATYA DHARMA BALUNG JEMBER - Moh. Agus Riawan; Muhammad Firdaus; Kasiman Kasiman (MBA - Journal of Management and Business Aplication, 2019)
Every    educational    institution,    wants    every    student    to    achieve    satisfactory achievements, achievements achieved by students are the main measurement tool and hope for knowing the success of an education. To further improvestudent learning achievement, it needs several ways to support the process of achieving that goal, and among the ways that can  be  taken  is  to  start  the  implementation  of  various  extracurricular  activities  in  each educational  institution.  Extracurricular  activities  are  a  series  of  programs  for  teaching  and learning  activities  outside  the  programmed  hours,  which  are  intended  to  improve  the perspective  of  students,  to  foster  talent  and  interest  and  to  serve  the  community.  For example:  in  Scouting  activities  is  a  form  of  activity  that  many  develop  humanitarian  and spiritual  activities  in  socializing,  including  cleanliness  of  the  environment,  providing assistance  to  people  who  are  in  disasters,  health  and  so  on.  The  article  is  intended  to investigate  the  extent to  which  teaching  styles  and  student  learning  motivation  influence partially and simultaneously on student achievement. The samples are 124studentsoutof248from  class  X  and  XI  students Satya  Dharma  High  School  Balung  Jember.  Data obtained  from questionnaires  and  documentation  were  analyzed  by  multiple  regression techniques. The results show that the teacher's teaching style and student learning motivation contribute  more  to  student  achievement.  However,  learning  motivation  has  more  dominant influence on student learning achievement than the teacher's teaching style. But this research only  discusses  concepts  and  conclusions  taken  from  the  relevant  researcher  hypothesis before.